Young Adolescents' Gender-, Ethnicity-, and Popularity-Based Social Schemas of Aggressive Behavior. (May 2016) - Clemans, Katherine H.; Graber, Julia A.
Social schemas can influence the perception and recollection of others' behavior and may create biases in the reporting of social events. This study investigated young adolescents' ( N = 317) gender-, ethnicity-, and popularity-based social schemas of overtly and relationally aggressive behavior. Results indicated that participants associated overt aggression with being male and African American and relational aggression with being female. In addition, participants associated all types of aggression with high perceived popularity. The strength of endorsement of several subscales differed significantly as a function of raters' gender and ethnicity. Findings highlight the importance of understanding how aggression-related social schemas may influence adolescents' reporting of peer behaviors.